How do honey bees handle their stress? A focus on their gut microbiota and immune system. (Apis mellifera subsp. capensis) - Lawson, Kayla (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.